PERAN KEPEMIMPINAN DALAM MENEGAKKAN DISIPLIN KERJA APARAT DESA (Studi Kasus di Desa Tewah Pupuh Kecamatan Benua Lima) Kabupaten Barito Timur (JAPB, 2022)
The role of leadership in the village government in carrying out its duties and obligations is assisted by village officials to run the wheels of the village government. Government Regulation Number 6 of 2014 concerning Villages, which contains "Village Government is the implementation of government affairs by the village government and the Village Consultative Body (BPD) in regulating and managing the interests of the local community based on the origins of local customs that are recognized and respected in the system. the government of the Unitary State of the Republic of Indonesia. The village government is the village head, and the village apparatus is an element of village government organizers. The village head must enforce the work discipline of village officials. In this study, problems were found related to the lack of discipline of village officials regarding working hours. This study aimed to determine the Role of Leadership in Enforcing the Work Discipline of Village Officials (Case Study in Tewah Pupuh Village, Benua Lima District) East Barito Regency. This study uses a qualitative method. Data collection techniques used are interviews, observation, and documentation. Using Hasibuan's theory (2017: 194) about eight indicators that affect work discipline: 1). Goals and abilities, 2). Exemplary leaders, 3). Retribution, 4). Justice, 5). supervision attached, 6). Firmness, 7). Legal Sanctions, 8). Human Relations. The results of this study indicate that the Role of Leadership in Enforcing Work Discipline for Village Apparatus (Case Study in Tewah Pupuh Village, Benua Lima District) East Barito Regency has played a significant role. Keywords: Leadership Role, Work Discipline